Development and Application of a High-Throughput Screening Method to Evaluate Antifungal Activity against Trichophyton tonsurans. (October 2015) - Preuett, Barry; Leeder, J. Steven; Abdel-Rahman, Susan
There exist relatively few drug classes on the market to treat dermatophyte infections. This investigation was designed to develop and validate high-throughput methodology for screening and confirmation of chemicals for activity against Trichophyton tonsurans . Growth characteristics were examined on two platforms (96- and 384-well) in three media at eight spore concentrations over a period of up to 120 h. Microspectrophotometry was used to automate plate reads. The 384-well platform was used to screen more than 7000 compounds from six chemical libraries. Z-scores for optical density relative to positive growth controls were used to flag compounds of interest and activity confirmed in separate assays. The final conditions selected for both screening and confirmation with minimum inhibitory concentration (MIC) determination were growth for 48 h at 32 °C in SabDex with 1 × 10 4 spores per reaction. Sensitivity and specificity averaged 99.2% (range, 95.2%−100%) and 99.8% (range, 99.1%−100%), respectively. MICs for known antifungals were similar to those reported by others using Clinical and Laboratory Standards Institute methods. Several novel compound classes were identified to have activity against T. tonsurans with potency comparable to known antifungals. A robust, reproducible assay is described that permits high-throughput screening in T. tonsurans .